The Great Canadian Grain Logistics Crisis of 2013-14 and Its Aftermath. Issue 2 (31st August 2018) - Rimmer AM, Peter J.; Comtois, Claude
Abstract : This study revisits the Great Canadian Grain Logistics Crisis of 2013-14 to explore the competitiveness of the country's grain exports. An approach to comprehending the dilemmas of the international grain supply chain and trade, and national logistics policy in an era of multinational corporations, draws upon the literature on global value chain analysis. This analysis identifies both the grain industry's global and local dimensions. An important literature on the 'politics' of the supply chain is also called into play to discuss who controls what aspects. This task of interpreting the various steps in Canada's grain logistics chain recognizes the key economic actors - producers, grain companies, railway companies, port terminal operators and export buyers - and political struggles between them as they each seek to maximize their self-interest. Policy implications for streamlining logistics operations are drawn from identifying where changes in the supply chain arrangements have gained or lost opportunities in export markets, particularly in the Asia-Pacific region.